Mind the (sr)GAP – roles of Slit–Robo GAPs in neurons, brains and beyond - Lucas, Bethany (J Cell Sci, 2017)
The Slit–Robo GTPase-activating proteins (srGAPs) were first identified as potential Slit–Robo effectors that influence growth cone guidance. Given their N-terminal F-BAR, central GAP and C-terminal SH3 domains, srGAPs have the potential to affect membrane dynamics, Rho family GTPase activity and other binding partners. Recent research has clarified how srGAP family members act in distinct ways at the cell membrane, and has expanded our understanding of the roles of srGAPs in neuronal and non-neuronal cells. Gene duplication of the human-specific paralog of srGAP2 has resulted in srGAP2 family proteins that may have increased the density of dendritic spines and promoted neoteny of the human brain during crucial periods of human evolution, underscoring the importance of srGAPs in the unique sculpting of the human brain. Importantly, srGAPs also play roles outside of the nervous system, including during contact inhibition of cell movement and in establishing and maintaining cell adhesions in epithelia. Changes in srGAP expression may contribute to neurodevelopmental disorders, cancer metastasis and inflammation. As discussed in this Review, much remains to be discovered about how this interesting family of proteins functions in a diverse set of processes in metazoans and the functional roles srGAPs play in human disease.